The implementation of projects for strengthening the profile of Pancasila students in the implementation of the independent learning curriculum - Lise Chamisijatin; Yuni Pantiwati; Siti Zaenab; Riantina Fitra Aldya (Journal of Community Service and Empowerment, 2023)
The independent curriculum begins to take effect in the 2022/2023 school year which requires a project to strengthen the profile of Pancasila students which is allocated around 25% of the total lesson hours per year. The partners for this community service activity are SMP Muhammadiyah 2 Batu City teachers, where they do not yet understand, design, document, report, and evaluate and follow up on projects. This service activity aims to assist the implementation of a project to strengthen the profile of Pancasila students in implementing the independent learning curriculum at SMP Muhammadiyah 2 Batu City. The method of implementing this service consists of 2 major activities, namely training and mentoring. The activities carried out as a solution for partners are: (1) Understanding of projects to strengthen Pancasila student profiles, (2) Designing implementation of projects to strengthen Pancasila student profiles, both in content and in terms of implementation time, (3) Implementing projects to strengthen Pancasila student profiles, and (4) Evaluate and follow up the project. All stages were carried out well, so it can be concluded that this service activity was able to increase teacher competence in implementing projects to strengthen Pancasila student profiles, which consisted of understanding, designing, documenting, reporting, and evaluating and following up on projects.